2017
DOI: 10.4236/oje.2017.79034
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Landscape Planning Considering Landscape Aesthetics (Case Study: Part of Tehran-Qom Freeway)

Abstract: Visual quality is a significant issue in today's modern world which needs to be evaluated. This assessment is based on the observer's perception and sight of space and attempts to introduce the criteria of spatial desirability in the landscape. Analysis of the relationships between visual quality and structural features of the landscape is an effective way of conducting cognitive research. For this purpose, the analysis of visual quality was considered by compiling measurement and evaluation criteria, based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Human beings have limited use of material resources. In order to meet the needs of daily life, it is necessary to find the maximum utilization value in the limited material materials, and regard the maximum value of materials as the technical demand [9]. In Figure 1, some eco-aesthetic landscapes are shown that both serve human beings and optimize and protect the environment.…”
Section: Idea Of Ecological Aestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human beings have limited use of material resources. In order to meet the needs of daily life, it is necessary to find the maximum utilization value in the limited material materials, and regard the maximum value of materials as the technical demand [9]. In Figure 1, some eco-aesthetic landscapes are shown that both serve human beings and optimize and protect the environment.…”
Section: Idea Of Ecological Aestheticsmentioning
confidence: 99%
“…Due to the obsolescence of the form and function of aesthetic products, the life of the product is often advanced, which brings huge losses to the material environment on which human The key to realizing this problem is to enhance consumers' awareness of environmental protection and enhance the aesthetic quality of products. There is a harmonious interaction between the two [12][13].…”
Section: Figure 1: Ecological Aesthetic Landscapementioning
confidence: 99%
“…Second, even within the papers included in our systematic review, five of the studies demonstrated features that could potentially disqualify them as Q + PPGIS studies, depending on the methodological definition employed. This includes Darabi et al ( 2017 ), who purport to conduct a Q-sort, but there is not clear evidence that the method they employed was a traditional Q study; Kangas et al ( 2014 ) who used their sort to analyse a participatory mapping-based method rather than integrating Q as part of their planning process; Dujardin et al ( 2018 ) who employed a process where GIS was used to generate hazard maps through public participation with unclear details on their mapping process; and Navrátil et al ( 2013 ) who used Q to sort landscape features and future scenarios then mapped the results based on the features themselves, as opposed to conducting participatory mapping activities. Future research needs to better elucidate Q + PPGIS approaches employed, to remove confusion about the use of the method.…”
Section: Limitations and Future Researchmentioning
confidence: 99%